THE MEDIATING ROLE OF COPING STRATEGIES BETWEEN SOCIAL-EMOTIONAL COMPETENCES AND PSYCHOLOGICAL WELL-BEING AND DISTRESS IN TEACHERS - Rodríguez Gómez, Alicia; Becerril, Marta; Privado, Jesús; Amorós Gómez, Montserrat; Argelagós, Esther (Bordón, Revista de Pedagogía, 2026)
INTRODUCTION. Teachers are a professional group especially exposed to high levels of stress leading to anxiety and depression problems. The development of their socio-emotional competences (SEC) and coping strategies can be considered essential personal resources that favour the possibility of responding to the high demands in the current educational context. The present study explores the mediating role of approach and avoidance coping strategies between socio-emotional competences and psychological well-being, distress, and teaching engagement. METHOD. The study was conducted in a sample of 395 primary, secondary, baccalaureate and university teachers of 45.07 years (SD = 17.95 years), 83.3% women, who completed a set of self-report questionnaires about the different variables studied. The data were analysed using confirmatory structural equation models to estimate the mediating role of coping strategies between socio-emotional competences and measures of psychological well-being, distress, and engagement. RESULTS. The mediation model showed a good fit with the data (Goodness of Fit Index = 0.955, Normed Fit Index = 0.932, Standardized Root Mean Square Residual = 0.117). Specifically, socio-emotional competences predicted directly and positively psychological well-being and engagement, and predicted negatively psychological distress. An indirect effect of socio-emotional competences on psychological well-being and engagement was found mediated by approach coping. In addition, another indirect effect of socio-emotional competences on psychological distress was found mediated by avoidance coping. DISCUSSION. The results of this study allow to consider the development of teachers’ socioemotional competences and approach coping strategies as important aspects to be included in the framework of their initial or in-service training in order to contribute to their psychological well-being and their engagement in schools.
El papel mediador del afrontamiento entre las competencias socioemocionales y el bienestar y malestar psicológicos en el profesorado
INTRODUCCIÓN. Los profesores son un colectivo profesional especialmente expuesto a altos niveles de estrés conducentes a problemas de ansiedad y depresión. El desarrollo de sus competencias socioemocionales y estrategias de afrontamiento pueden considerarse recursos personales imprescindibles que favorecen la posibilidad de dar respuesta a las altas demandas en el contexto educativo actual. El presente estudio explora el rol mediador de las estrategias de afrontamiento de carácter aproximativo y evitativo entre las competencias socioemocionales y el bienestar y malestar psicológicos y el engagement docente. MÉTODO. El estudio se realizó en una muestra de 395 profesores de primaria, secundaria, bachillerato y universidad de 45,07 años (DT = 17,95 años) y un 83,3 % de mujeres, quienes respondieron un conjunto de cuestionarios de autoinforme sobre las diferentes variables estudiadas. Los datos fueron analizados mediante modelos de ecuaciones estructurales de carácter confirmatorio para estimar el efecto mediacional de las estrategias de afrontamiento entre las competencias socioemocionales y las medidas de bienestar y malestar psicológicos y el engagement. RESULTADOS. El modelo mediacional mostró un buen ajuste de los datos (GFI = 0,955, NFI = 0,932, SRMR = 0,117). Concretamente, las competencias socioemocionales predijeron de forma directa y positivamente el bienestar psicológico y el engagement y negativamente el malestar psicológico. Se obtuvo un efecto indirecto de las competencias socioemocionales sobre bienestar psicológico y engagement, mediado por el afrontamiento de aproximación. Además, se obtuvo otro efecto indirecto de las competencias socioemocionales sobre malestar psicológico, mediado por el afrontamiento de evitación. DISCUSIÓN. Los resultados de este estudio permiten considerar el desarrollo de las competencias socioemocionales y las estrategias de afrontamiento de carácter aproximativo de los docentes como importantes aspectos a incluir en el marco de su formación inicial o permanente con el objetivo de contribuir a su bienestar psicológico y engagement.
Keywords: emotional intelligence; coping; well-being; stress variables; teachers; structural equation model; inteligencia emocional; afrontamiento; bienestar; variables de estrés; profesores; modelo de ecuaciones estructurales